Low Altitude Remote Sensing and its Application in Precision Agriculture: A Case of Nzathu Farm in Traditional Authority Somba in Blantyre District, Malawi - Chilonga, Donnex; Kiswisch, Manuel (My University, 2016)
The practical application of Low Altitude Remote Sensing (LARS) in Precision Agriculture (PA) has tremendously gained ground recently. This is despite concerns about the viability of such systems for farmers related to the costs of both the system and the image processing software, technical expertise to operate the LARS and processing of the imagery itself, and timely delivery of information which is greatly compromised by not only the unstable and expensive internet facility but also local weather conditions such as wind and clouds. Using image analysis, this study illustrates the utilization of self-build unmanned aerial vehicle (UAV) in monitoring crop conditions in farmers’ fields in the area of Traditional Authority Somba in Blantyre district of Southern Malawi. It demonstrates that both optical and near-infrared imageries obtained from LARS can be used to monitor fertilizer trials, conduct crop investigation and mapping of field surface drainage.
Keywords: Low Altitude Remote Sensing; Unmanned Aerial Vehicle (UAV); Global Positioning System (GPS); Geographic Information Systems (GIS); Precision Agriculture; Soil fertility; Maize; Crop Monitoring; Somba; Blantyre; Malawi